2012
DOI: 10.1029/2011jd017393
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanic acid in a global chemistry transport model: Tropospheric distribution, budget, and identification of regions with potential health impacts

Abstract: [1] This study uses a global chemical transport model to estimate the distribution of isocyanic acid (HNCO). HNCO is toxic, and concentrations exceeding 1 ppbv have been suggested to have negative health effects. Based on fire studies, HNCO emissions were scaled to those of hydrogen cyanide (30%), resulting in yearly total emissions of 1.5 Tg for 2008, from both anthropogenic and biomass burning sources. Loss processes included heterogeneous uptake (pH dependent), dry deposition (like formic acid), and reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 57 publications
2
79
0
Order By: Relevance
“…Dry deposition is a major sink of HNCO (Roberts et al, 2014;Young et al, 2012), although HNCO readily partitions into the aqueous phase (H = 10 5 mol L −1 atm −1 ), where it can hydrolyze to NH 3 . We estimate that aqueous partitioning of HNCO was negligible.…”
Section: Isocyanic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry deposition is a major sink of HNCO (Roberts et al, 2014;Young et al, 2012), although HNCO readily partitions into the aqueous phase (H = 10 5 mol L −1 atm −1 ), where it can hydrolyze to NH 3 . We estimate that aqueous partitioning of HNCO was negligible.…”
Section: Isocyanic Acidmentioning
confidence: 99%
“…HNCO is of growing interest because exposure levels > 1 ppb v are linked to various human health issues, including atherosclerosis, cataracts, and rheumatoid arthritis (Jaisson et al, 2011;Roberts et al, 2011). Primary emission and secondary photochemical production sources of gas-phase HNCO have been identified and reported (Borduas et al, 2013;Roberts et al, 2014), but the magnitudes of these sources remain highly uncertain (Young et al, 2012). Combustion processes, including biomass burning, gasoline/diesel fuel combustion, and tobacco smoke are a primary source of HNCO (Roberts et al, , 2014Link et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient isocyanic acid mixing ratios of typically 100 pptv have been measured (Roberts et al, 2013), while mixing ratios above 1 ppbv were found in the plumes from biomass burning or in regions impacted by domestic wood burning and wild fires (Young et al, 2012;Roberts et al, 2013). Several countries regulate the occupational exposure from isocyanates but no explicit guidelines exist for the ambient health risk.…”
Section: Relevance For the Health Risk Assessmentmentioning
confidence: 99%
“…Historically, biomass burning was considered to be the dominant global source of both 5 HNCO (Veres et al, 2010;Roberts et al, 2011;Young et al, 2012) and HCN (Li et al, 2000;Li et al, 6 2003;Li et al, 2009;Shim et al, 2007). Global HCN (Li et al, 2003) and HNCO (Young et al, 2012) 7 models have hitherto considered vehicle sources of these compounds to be negligible.…”
Section: Used the 41mentioning
confidence: 99%